Indonesia's Trade Policy In Responding To Free Trade In The Midst of Uncertain Conditions - Rubiati, Rubiati; Satria Unggul Wicaksana , Satria Unggul Wicaksana (Journal of Private and Commercial Law, 2024)
Free trade widens the gap between developed and developing countries, according to Global Food Security Index data, Indonesia is ranked fourth in ASEAN with a score of 60.2. Indonesia's score is still low compared to the global average of 62.2. It is necessary to emphasize the role of the government to realize laws and policies with the right budget allocation to encourage the performance of a more competitive business environment. This research answers the politics of free trade law amid uncertain conditions in Southeast Asia and the Indonesian government's protection of business people in free trade. By using socio-legal research methods based on an interdisciplinary approach, the author realizes that normative legal research is not enough to analyze free trade policies, so socio-legal research is needed to explain the relationship between law and community facts comprehensively. The results of this study answer that Indonesia as a member of the Association of Southeast Asian Nations (ASEAN) which has currently developed the ASEAN Free Trade Area (AFTA) policy seeks to reduce intra-regional tariffs among its members through the Common Effective Preferential Tariff (CEPT) Scheme. The World Trade Organization (WTO) is expected to bridge all the interests of countries in the world in the trade sector. Legal protection for business people exists because of the legality of the business. One form of protection of the Indonesian government is the promulgation of various legal regulations governing economic activities and free trade.